Effectiveness of Sexual Harassment Risk Reduction Education based on Health Belief Model: A Quasi Experimental Study - Thapaliya, Radhika; Adhikari, Samir Kumar (Journal of Karnali Academy of Health Sciences, 2020)
Background: Sexual harassment is a public health problem which has serious effects to girls’ psychosomatic health. Due to social stigma and lack of skills, even the girls can’t refuse sexual harassment. This study was done to evaluate the effectiveness of sexual harassment risk reduction education based on Health Belief Model. Methods: A quasi experimental study was conducted in secondary level public schools of Tokha Municipality, Kathmandu. The study was done from 5th February 2016 to 5th May 2016. The sample size was 117 for each group which was calculated with input of 95% CI, power of test=80%, assuming 38 % change based on baseline study and 10% nonresponse rate. The ratio of participants in intervention and control group was 1:1 and the total numbers of participants were 128 in pretest and 121 in posttest at the intervention group and 131 in pretest and 122 in posttest in the control group. Data was collected by using self-administered questionnaire for knowledge and likert’s scale was used for attitude and behavioural intention. Lecture, group discussion, role play and brainstorming were methods used for intervention. After two weeks of intervention, a post-test was done. Results: Testing of hypothesis revealed that the knowledge about sexual harassment, anti-sexual harassment attitude and behavioural intention of using refusal skills in sexual harassment in the intervention group were significantly higher than that of control groups i.e. p<0.001, p<0.001 and p<0.05 respectively. Conclusion: Sexual harassment risk reduction education intervention based on health belief model is effective to increase the knowledge, attitude and behavioural intention of participants. The findings of the study encourage further exploring creative approaches to programming in other violence prevention areas.